DESCRIPTION OF STIGMA FOR STUNTING CHILDREN - Agung Widiastuti; Muzaroah Ermawati Ulkhasanah; Fakhrudin Nasrul Sani; Anisa Yuli Kartikasari (Proceeding of International Conference on Science, Health, And Technology, 2022)
Stunting experienced by children will have a serious impact on the health of children's growth and development. Children with stunting will experience both cognitive and motor disorders which will have an impact until adulthood, one of which is the impact of productivity. The aim is to describe the stigma associated with children with stunting. Research method: This study is a descriptive study, the number of samples as many as 113 respondents sampling technique with purposive sampling probability. Results: The results showed that most stunting children received negative stigma. Stunting children tend to get less favorable treatment from their friends. Conclusion: Stunting children who get negative stigma are at greater risk of experiencing low self-esteem and having an emotional attitude